2014
DOI: 10.1186/1749-8090-9-44
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of single incision thoracoscopic surgery: early experience of 264 cases

Abstract: BackgroundSingle incision thoracoscopic surgery (SITS) is recognized as a difficult procedure and surgeons hesitate to perform this technique. We describe our experience of SITS and determine whether SITS can be a routine approach in minimally invasive surgery.MethodsFrom May 2011 to April 2013, a single operator attempted SITS for 264 cases. Their medical records were retrospectively reviewed with regard to age, sex, diagnosis, operation time, hospital stay, need of additional incision, morbidity, and early o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although uVATS has been increasingly adapted for the management of recurrent uncomplicated pleural effusions, preoperative staging in lung cancer, treatment of primitive spontaneous pneumothorax, palmar hyperhidrosis and even for complex anatomic lung resections (19,20), surprisingly little is published about its use in empyema. An early publication by Song et al, reported that a uniportal approach in empyema was difficult and resulted in a 50% conversion rate to cVATS or thoracotomy (21). Subsequent studies showed lower conversion rates of around 10% (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although uVATS has been increasingly adapted for the management of recurrent uncomplicated pleural effusions, preoperative staging in lung cancer, treatment of primitive spontaneous pneumothorax, palmar hyperhidrosis and even for complex anatomic lung resections (19,20), surprisingly little is published about its use in empyema. An early publication by Song et al, reported that a uniportal approach in empyema was difficult and resulted in a 50% conversion rate to cVATS or thoracotomy (21). Subsequent studies showed lower conversion rates of around 10% (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a small series (11 patients), Song et al reported a high conversion rate (55%) due to the difficulties encountered in removing the thickened visceral pleura. For this reason, they used more frequently a three portal conventional VATS approach for removal of fibrous peel [19]. Marra et al [20] developed an original 'hybrid' technique of single access thoracoscopy using a classical video-mediastinoscope to debride the cavity and disrupt all pleural septation.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the incision in uniportal cVATS is important as it affects the complexity of the surgery (7,8). Our surgical incision was made at the fifth intercostal space on the midaxillary line, and was based on our previous experience.…”
Section: Commentsmentioning
confidence: 99%